Virtual voyage: Unveiling the ‘3I’ influence on student learning - Shuangshuang Fan; Shali Wang; William Mbanyele; Yu Chen; Shunfang Miao; Ruping Long (PLoS ONE, 2025)
This study delves into the multifaceted “3I” technological attributes of metaverse classrooms—namely perceived immersion, perceived interaction, and perceived imagination—and their interplay with psychological imagery and representational ability. This investigation seeks to elucidate the nexus between these constructs and their collective influence on students’ learning outcomes. To achieve this, an integrative conceptual model has been meticulously constructed, encapsulating the dynamic interrelationships between the “3I” characteristics and the pivotal cognitive factors of psychological imagery and representational ability. Employing a Partial Least Squares Structural Equation Modeling (PLS-SEM) approach, an empirical inquiry was conducted on a dataset comprising 930 meticulously validated questionnaires. The analysis yielded significant findings: perceived immersion and perceived interaction were found to exert a direct and positive influence on learning outcomes. Furthermore, psychological imagery emerged as a central mediator in the pathway from metaverse classroom characteristics to learning outcomes. Representational ability was identified to have dual roles, exerting both positive and negative moderating effects on the relationship between perceived imagination and learning outcomes, as well as between psychological imagery and learning outcomes.The study’s empirical evidence offers substantial theoretical and empirical validation for the practical application and strategic refinement of metaverse-based educational practices. It underscores the imperative to account for individual differences and to foster immersive and interactive learning environments. Additionally, the study highlights the untapped potential of perceived imagination in enhancing learning outcomes, suggesting a rich vein for future research.